The Environmental Surveillance System of nCOVID-19 and Animal Coronaviruses (TGEV and MHV) for Mitigating the Further Spreading - Mohammed, Asmaa N. (Journal of Advanced Veterinary Research, 2020)
Coronavirus disease 2019 (nCOVID-19) is a newly emerging disease first discovered in Wuhan city, China, in December 2019. Currently, nCOVID-19 has become a global health concern causing severe respiratory tract infection besides animal coronaviruses includes transmissible gastroenteritis virus (TGEV) and mouse hepatitis virus (MHV). Implementing of surveillance system requires coordination and collaboration between the Centers for Disease Control and Prevention (CDC), local, and state public health authorities. Outbreak surveillance can help to mitigate the further spreading of coronaviruses in the environment. nCOVID-19 can persist on inanimate surfaces up to 9 days whilst animal coronaviruses (TGEV and MHV) can persist in the environment for ≥ 28 days at 4°C. Effective surface disinfection may help to ensure an early containment and prevention of further viral spread. Some biocidal agents efficiently inactivate coronavirus infectivity within minutes such as ethanol 70%, hydrogen peroxide (H2O2) 0.5%, and sodium hypochlorite (NaOCl2) 0.1%. This review article was designed to address the environmental surveillance system focused on the persistence of new coronavirus (nCOVID-19) and animal coronaviruses (TGEV and MHV) on the environmental surfaces, factors affecting their survival, and assess the efficiency of different biocidal agents against coronaviruses to establish an efficient control strategy.